ANALISIS MOTIVASI, KOMPETENSI, DAN DISIPLIN KERJA TERHADAP KINERJA GURU DI SMP AL-ISLAM 1 SURAKARTA - Isnarizal Shoim; Eny Kustiyah; Sudarwati Sudarwati (ITB AAS INDONESIA Surakarta, 2019)
The purpose of this study was to determine the effect of motivation, competence, and work discipline on teacher performance. This study includes a type of quantitative research that explains the relationship between variables and testing hypotheses. The population in this study were all teachers at Al-Islam 1 Middle School in Surakarta, totaling 63 people. The entire population is taken as a sample. Methods of collecting data using a questionnaire. The data analysis technique uses multiple linear regression analysis. The results of the study show that: (1) Motivation, competence, and work discipline simultaneously have a significant effect on the performance of teachers in Surakarta Al-Islamic Middle School 1. Teacher performance will increase if teachers have high work motivation, good and appropriate teaching competencies, and have high discipline in work; (2) Motivation has a positive effect on teacher performance at Surakarta Al-Islam Middle School. The higher the motivation to teach, the higher the teacher's performance; (3) Competence has a positive effect on teacher performance at Surakarta Al-Islam Middle School. The higher the teaching competency, the higher the teacher's performance; (4) Work discipline has a positive effect on teacher performance at Surakarta Al-Islamic Middle School 1. The higher the work discipline, the higher the teacher's performance. Keywords: teacher performance, motivation, competence, work discipline